DINOFLAGELLATE CYSTS AND CALCAREOUS NANNOFOSSILS FROM THE UPPER CRETACEOUS SARACENO FORMATION (CALABRIA, ITALY): IMPLICATIONS ABOUT THE HISTORY OF THE LIGURIDE COMPLEX - STEFANO TORRICELLI; MARIA ROSA AMORE (Rivista Italiana di Paleontologia e Stratigrafia, 2003)
Organic-walled dinoflagellate cysts and calcareous nannofossils recovered from the turbidites of the Saraceno Formation outcropping in the type area (north-eastern Calabria, Italy) are presented. They provide new information about the age of the Saraceno Formation, hence a constraint to reconstruct the timing of deformations that affected the Liguride Complex. The distribution of dinoflagellate cysts and calcareous nannofossils in the succession studied is compared with biostratigraphies available for the Upper Cretaceous. Accordingly, the age of the lowermost part of the Fiumara Saraceno section is latest Albian to Turonian, whereas the upper part of the section is dated as late Campanian-?earliest Maastrichtian. A hiatus spanning che Coniacian, che Santonian and most of che Campanian is inferred between these two successions, which are also distinguished by the presence and absence of flint respectively. Consistencies and discrepancies of che present data with biostratigraphical information previously published for che Saraceno Formation, are discussed.